Inward FDI from Asean and its implication on Malaysian manufacturing sector - Mohd Khairul Hisyam Hassan,; Tajul Ariffin Masron, (Penerbit Universiti Kebangsaan Malaysia, 2011)
Regional FDI or south-south FDI refers to inflows of PDI from developing countries to another developing country; and it is gaining importance and is growing over time. This can be observed from the increasing amount of outward FDI from developing countries. Without exception, the ASEAN region is also contributing more to outward FDI. While there is an abundance of researches dealing with the inflows of PDI from developing countries. As alarge chuck of FDI from ASEAN neighboring countries, it is the aim of this studyto investigate the impact of intra-ASEAN inward FDI on Malaysian manufacturing sector.